Choreotherapy in the complex correction of motor stereotype in persons with down syndrome under inclusion conditions - Romanov K.P.; Parfenova L.A.; Shaimieva A.D. (Theory and Practice of Physical Culture, 2023)
Objective of the study: to evaluate the effectiveness of complex correction of motor stereotype in persons with Down syndrome (DM) in the process of practicing choreotherapy in inclusion conditions. Methodology and organization of the study. Within the framework of the Inclusive Sports Saturday project (2021-2022), a sequential experiment was conducted to study the influence of choreotherapy classes based on the use of complex movements combined into one semantic sequential, rhythmic, motor act in order to correct postural posture control in people with Down syndrome. The results of the study and conclusions: Classes with children with diabetes according to the method of choreotherapy allow you to actively engage and develop such qualities as mechanical memory, imitative abilities, musical memory, sense of rhythm, actively affects the vestibular system, improves muscle tone and coordination of movements, which generally has a positive effect on the formation of correct posture.